A comparative study of hydrogen-induced crackingresistances of API 5L B and X52MS carbon steels - Figueredo, Rodrigo Monzon; de Oliveira, Mariana Cristina; de Paula, Leandro Jesus; Acciari, Heloisa Andréa; Codaro, Eduardo Norberto (Elsevier, 2019)
Susceptibility to hydrogen-induced cracking of API 5L B and X52MS low-carbon steels inNACE 177-A, 177-B and 284-B solutions has been investigated by the present work. A met-allographic analysis of these steels was performed before and after NACE TM0284 standardtesting. Corrosion products were characterized by scanning electron microscopy and X-raydispersive energy spectrometry, which were subsequently identified by X-ray diffraction.Thus it was found that pH directly affects the solubility of corrosion products and hydrogenpermeation. Both steels showed generalized corrosion in solution 177-A, and a discontin-uous film was formed on their surfaces in solution 177-B, however, only the API 5L B steelfailed the HIC test and exhibited greater crack length ratio in solution 177-A. In solution284-B whose pH is higher, the steels exhibited thick mackinawite films with no internalcracking.
Keywords: Hydrogen embrittlement; Hydrogen sulfide; Hydrogen-induced cracking; Low carbon steel; Sour corrosion